Энергетические соотношения в автономном асинхронном генераторе при работе в импульсных системах электроснабжения - Мазуренко, Александр Григорьевич; Паляниченко, Иван Кондратиевич; Кравчук, Анатолий Федорович; Резцов, Виктор Федорович (My University, 1993)
Приведены результаты исследования энергетических характеристик автономного асинхронного генератора в импульсных системах электроснабжения. Дана методика выбора оптимального режима работы генератора при периодических разрядах емкостных накопителей. Разработаны рекомендации по выбору параметров машины для импульсных систем.

There given results of the investigation of the energy performance of Autonomous asynchronous generator in pulse power supply systems. There given the technique of a choice of an optimum mode of work of the generator in the periodic discharges of capacitive drive. Were received the recommendations at the choice of the parameters of the machine for pulse-modulated systems.
Keywords: генератор асинхронный; generator asynchronous; накопители емкостные; импульсный режим; pulse mode; power supply system; кафедра електропостачання і енергоменеджменту